Sistem Pencatatan Kehadiran Deteksi Wajah Menggunakan Metode Haar Feature Cascade Classifier - Miftah Khul Janah; Veronica Lusiana (Jurnal Ilmiah Giga, 2021)
Biometric innovation is one source that can be used in security frameworks such as facial recognition as personal information. The human face has a lot of data and has the most normal and widely used attributes for the presentation of human character. As well as communicating feelings and considerations, faces can also be used to identify individuals. One of the innovations in the recognition statement applied to biometrics is the use of the human face as a recording system in the field of education. However, there are several circumstances related to the recording of student absenteeism currently occurring in the field of education, namely "Titip Absent". Therefore, in this study proposed a system that uses a student attendance recording system using computer technology to reduce the level of cheating when filling in attendance forms and the effectiveness of student data processing, the Haar Cascade classification method is used to record the student attendance process using a biometric system. The algorithm applied in the Haar Cascade classifier method uses a face detector called the "Cascade Classifier". The result of this study is an attendance application that can detect whether all users who have recorded attendance have been registered in the system with the distance between the face and the camera is 50 cm with an accuracy rate of 70%.